Climate related diseases. Current regional variability and projections to the year 2100 - Błażejczyk, Krzysztof; Baranowski, Jarosław; Błażejczyk, Anna (Quaestiones Geographicae, 2019)
The health of individuals and societies depends on different factors including atmospheric conditions which influence humans in direct and indirect ways. The paper presents regional variability of some climate related diseases (CRD) in Poland: salmonellosis intoxications, Lyme boreliosis, skin cancers (morbidity and mortality), influenza, overcooling deaths, as well as respiratory and circulatory mortality. The research consisted of two stages: 1) statistical modelling basing on past data and 2) projections of CRD for three SRES scenarios of climate change (A1B, A2, B1) to the year 2100. Several simple and multiply regression models were found for the relationships between climate variables and CRD. The models were applied to project future levels of CRD. At the end of 21st century we must expect increase in: circulatory mortality, Lyme boreliosis infections and skin cancer morbidity and mortality. There is also projected decrease in: respiratory mortality, overcooling deaths and influenza infections.